Factors Influencing Passengers' Purchase Intention Towards App-Cab Services in Metro Cities of India : A Study on Smartphone Users - Chakraborty, Debarun (Indian Journal of Marketing, 2021)
This study aimed to find out that which were the factors influencing the passengers to purchase the app-cab services in metro cities of India. The responses were collected from smartphone users only. Stratified random sampling method was used, and 276 respondents participated in the study. The responses were collected from Kolkata, Delhi, Chennai, and Mumbai (the metropolitan cities of India). Exploratory factor analysis (EFA) followed by multiple regression analysis (MRA) were used to obtain the final results. The study results revealed that Availability & Convenience was the most influencing factor when passengers opted for app-cab services and it had a significant and positive effect on booking app-cabs by smartphone users. The results also revealed that the factor named Security did not have any impact on booking of app based cabs. The study revealed that the administrators need to keep an eye on driver’s behavior and should train them properly. To increase their market share, the app - cab service providers need to provide coupons or discount options to attract riders.